Identification of Factors Causing Student Misconceptions Using Five-Tier in the Material Exploring Cells for Grade XI: Identifikasi Faktor Penyebab Miskonsepsi Siswa dengan Menggunakan Five-Tier pada Materi Menjelajah Sel Kelas XI - Habsari, Khusna Yurdhika; Sumarno; Rahayu, Praptining (BIO-EDU: Jurnal Pendidikan Biologi, 2025)
Misconception is one of the problems that is often found in the learning process, this is because of the discrepancy between the concepts that students have with the actual concept. Misconceptions that continue to occur without realizing it will cause students difficulty in receiving learning. This study aims to identify the factors that cause misconceptions that occur in students using the Five-Tier test and questionnaire. The population in this study were students of grade XI of SMA Negeri 1 Jakenan. The sample in the study were students of class XI-10 SMA Negeri 1 Jakenan. The sampling technique used was purposive sampling. The data collection method used a five-tier question instrument to measure misconceptions in students and their sources and a questionnaire instrument was used to find out the causes of misconceptions in students. The results showed that 21.76% of students had misconceptions. Based on the results of research using a five-tier question, the sources of information used by students in answering the questions were highest from personal thoughts of 80.38%, teachers 0.48%, internet 8.92, friends 17.94%, and books 5.61%. The results obtained from the question are directly proportional to the results of the causes of misconceptions using questionnaire instruments, based on questionnaire data, the percentage of causes of misconceptions is 61.11% from students, 15.56% from teachers, 40.56% from the internet, 45% from friends, and 25% from books.